Adult-Onset Still’s Disease in Clinical Practice of Infectious Diseases: A Case Report - Đurić, Milivoje Jovan; Makevic Djuric, Mirjana; Pavlovic, Mirjana (Medicinski časopis, 2024)
Adult-onset Still's disease is a rare autoimmune disorder accompanied by a triad of fever, exanthema, and arthralgia. In addition to this dominant presentation, it has a wide spectrum of clinical symptoms, with extensive involvement of multiple organs. Because of this diagnostic of adult-onset Still's disease remains one of exclusion and fulfilling sets of diagnostic criteriaWe report on the case of a 20-year-old female who was initially treated for a suspected allergic reaction to a drug and then referred to an infectious disease specialist as Fever of unknown origin accompanied with rash.
Keywords: adult onset Still’s disease, fever, rash, arthritis.